THE INFLUENCE OF THE IMPLEMENTATION OF SAFETY, HEALTH AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE - Siregar, Sadrak; Yuliaty, Farida; Kartamiharja, Sobarna; Kosasih, Kosasih; Paramarta, Vip (HEARTY, 2025)
Starting from the emerging phenomenon showing signs of declining levels of occupational safety, occupational health and motivation and company performance since 2019 where there was an outbreak of disease that caused only 50 people to work and the rest had to be quarantined. So interested in conducting this research. This study aims to obtain empirical evidence about the effect of safety, health and motivation on employee performance at PT. Kapur Putih Negeri Katon-Pesawaran, Lampung Province. The method used is descriptive verification analysis and multiple linear regression analysis. Data collection using questionnaires distributed to all employees with the technique of the entire population being the subject of the study. The number of respondents was 80 people who worked at PT. Kapur Negeri Katon Pesawaran, Lampung Province. The results of the analysis show that safety, health, motivation and performance are generally classified as good. The results of the verification analysis both partially show that safety has a positive effect on performance, health shows a positive effect on employee performance and motivation has a positive effect, so the researcher suggests that it needs to be improved again.